THE ASSESSMENT OF EFFECTS OF COMBINED THERAPY WITH MILDRONATE ON LIPID PROFILE, INFLAMMATORY FACTORS AND ENDOTHELIUM FUNCTION IN PATIENTS WITH ISCHEMIC HEART DISEASE - I. V. Sergienko; V. V. Kukharchuk; S. A. Gabrusenko; V. V. Malakhov; V. P. Masenko; M. I. Tripoten; T. V. Balahonova (Рациональная фармакотерапия в кардиологии)
Aim. To study the effect of treatment with metabolic corrector mildronate on lipid profile, inflammatory factors and endothelium function in patients with ischemic heart disease (IHD).Material and methods. 60 patients with IHD (stable exertional angina, II-IV functional class) were included in to the study. They were split in two groups. Patients of the main group (n=30) were treated with mildronate (1000 mg per day during 3 months) combined with standard therapy. Patients of the second group (n=30) received the standard therapy only. Total cholesterol (TC), triglycerides (TG), cholesterol of low density lipoproteid (LDL-C), cholesterol of high density lipoproteid (HDL-C), aspartate aminotransaminase (AST), alanine aminotransaminase (ALT), creatine kinase (CK), C-reactive protein (CRP), interleukin-6 (IL-6), lipoprotein (α) (Lp(α)), NO3 were determined. Besides endothelium dependent vasodilatation of brachial artery was studied.Results. TC, HDL-C and TG levels did not differ before and after treatment with mildronate, but LDL-C level significantly reduced (from 3.06±1.32 to 2.7±1.0 mmol/l, p<0.05) in IHD patients after 3 months of mildronate treatment. There was significant decrease in CRP level (from 1.5±1.8 to 1.0±1.1 mg/l, р<0.01) and absent of IL-6 level difference (before treatment – 3.7±2.3 and after treatment – 3.4±1.8 pg\ml, p>0.05). The significant change of Lp(α) was not found in both groups. Increase in endothelium dependent vasodilatation was noted after mildronate treatment. Besides increase in NO3 level in blood was detected (from 33.5±10.0 to 44.1±32.3 µmol/l, р<0.05).Conclusion. Data of the study demonstrated that metabolic correctors exert positive influence on lipid profile and inflammatory factors in patients with IHD.